2005
DOI: 10.1089/jpm.2005.8.1016
|View full text |Cite
|
Sign up to set email alerts
|

Communication about End-of-Life Care between Language-Discordant Patients and Clinicians: Insights from Medical Interpreters

Abstract: These results provide insights for physicians about how to improve end-of-life discussions with language-discordant patients and their families. Interpreter recommendations provide physicians and health care organizations with specific tools that may improve quality of communication about end-of-life discussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
118
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(119 citation statements)
references
References 23 publications
1
118
0
Order By: Relevance
“…In a community-based study, families reported that nurses were more likely to have discussed symptoms and their treatment than physicians and that discussions with nurses were more understandable than those with physicians. 24 These data confirm the importance of nurses in the communication and coordination of care for dying patients and their family members. Our findings support the need to expand nurses' skills and to offer opportunities to participate in end-of-life communication as a way to improve the quality of end-of-life care.…”
Section: Discussionmentioning
confidence: 57%
“…In a community-based study, families reported that nurses were more likely to have discussed symptoms and their treatment than physicians and that discussions with nurses were more understandable than those with physicians. 24 These data confirm the importance of nurses in the communication and coordination of care for dying patients and their family members. Our findings support the need to expand nurses' skills and to offer opportunities to participate in end-of-life communication as a way to improve the quality of end-of-life care.…”
Section: Discussionmentioning
confidence: 57%
“…Interpreters reported that complexity of information, information overload, and lack of clinician sensitivity toward the cultural and socioeconomic backgrounds of families with limited English were their primary challenges. Within the palliative care setting, Norris, Wenrich, Nielsen, Treece, Jackson and Curtis (2005) conducted a large qualitative study of 68 professional medical interpreters in the US about communication about end of life care. These interpreters emphasized the importance of both doctor and interpreter conveying compassion when delivering bad news.…”
Section: Introductionmentioning
confidence: 99%
“…We used a previous qualitative study with interpreters as a basis for survey development and included questions about specific experiences and attitudes toward interpreting discussions about end-of-life issues that were raised by interpreters in focus groups. 13 Prior to administration, the survey was pilot-tested with a group of interpreters employed at a public hospital in California that serves a large population of LEP patients. The pilot-testers endorsed the survey as being clear and not burdensome to complete.…”
Section: Survey Developmentmentioning
confidence: 99%
“…12 Data from qualitative research with interpreters suggest that languagediscordant discussions about end-of-life issues require unique skills from physicians and interpreters, including sensitivity to cultural cues related to death and dying and the ability to negotiate perceived tensions in the interpreter's role between providing strict interpretation versus acting as a cultural broker or an advocate for the patient and family. 13,14 Interpreters also report difficulty handling their own emotions and not feeling like a part of the health care team when interpreting for discussions about death and dying or delivering bad news. 13 The growing awareness of such challenges and the increasing frequency of these situations call for a deeper understanding of the experiences of interpreters in these uniquely difficult conversations in order to improve the quality of interpretation and the quality of care.…”
mentioning
confidence: 99%
See 1 more Smart Citation